The world food economy in the twenty-first century : challenges for international co-operation - de Haen, Hartwig...[et al.] (2003)
Focuses on the implications of the fundamental changes in the world food economy for international co-operation in food and agriculture. Concentrates especially on the FAO, and reviews the responses in monitoring, advocacy, resource mobilisation, regulation and technical and policy assistance activities.